Special interest groups & growth: A meta-analysis of Mancur Olsons theory - Theresa Hager (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
This thesis treats the theory of Mancur Olson on the relationship between interest groups and growth and the empirical analyses regarding its validation. Mancur Olson has developed a comprehensive theory of economic growth that grounds on his 1965 published book The Logic of Collective Action. Herein the mechanisms and dynamics of interest groups and collective action are elaborated and discussed. The subsequent complex theory of economic growth presented in The Rise and Decline of Nations (1982) shows the impact of the prevailing constellation of interest groups in a country on its economic prospects. The book lead to widespread discourse and criticism and its conclusions were analyzed multiple times with econometric methods. However, the research presents divergent results as to whether Olson's theory can be validated or not. The thesis gives an overview of Olson's theories and then discusses the criticism raised by other authors and own considerations. A meta-regression analysis is performed to synthesize the diverging results of various studies. Meta-regression analysis is a relatively new concept in economics. Its objective is to look at econometric evidence from a meta perspective and to use regression tools to find out if study characteristics exert an influence on the findings. It filters out the biases and allows a more objective view. The analysis is carried out on two levels: on the macro level using study characteristics and descriptive statistics and on the micro level using single regression results in a binary logistics model. The results allow a more differentiated look on Olson's theory and its tests. It is suggested that the theory is too comprehensive and complex to be covered by econometric methods. Therefore, any proper testing should include an examination of convoluting institutional aspects. – – Diese Arbeit behandelt die Theorie von Mancur Olson über die Beziehung zwischen Interessengruppen und Wachstum und die empirischen Analysen bezüglich ihrer Validierung. Mancur Olson hat eine umfassende Wachstumstheorie entwickelt, die auf seinem 1965 veröffentlichten Buch The Logic of Collective Action basiert. Darin werden die Mechanismen und Dynamiken von Interessengruppen und kollektivem Handeln herausgearbeitet und diskutiert. Die in The Rise and Decline of Nations (1982) vorgestellte komplexe Theorie des Wirtschaftswachstums zeigt den Einfluss der vorherrschenden Konstellation von Interessengruppen in einem Land auf seine wirtschaftlichen Perspektiven. Das Buch führte zu einem weit verbreiteten Diskurs und kritischen Anmerkungen. Seine Schlussfolgerungen wurden mehrfach mit ökonometrischen Methoden analysiert. Allerdings sind sich Forscher nicht einig, ob Olson's Theorie validiert werden kann oder nicht. Die Arbeit gibt einen Überblick über Olsons Theorien und diskutiert dann die Kritik anderer Autoren und eigene Überlegungen. Eine Metaregressionsanalyse wird durchgeführt, um die divergierenden Ergebnisse verschiedener Studien zu synthetisieren. Ziel ist es, ökonometrische Evidenz aus einer Meta-Perspektive zu betrachten und mit Hilfe von Regressionstools herauszufinden, ob Studienmerkmale einen Einfluss auf die Ergebnisse haben. Sie filtert die Verzerrungen heraus und ermöglicht eine objektivere Betrachtung. Die Analyse erfolgt auf zwei Ebenen: auf der Makroebene anhand von Studienmerkmalen und deskriptiver Statistiken und auf der Mikroebene anhand einzelner Regressionsergebnisse und einem binären Logistikmodell. Die Ergebnisse erlauben einen differenzierteren Blick auf Olsons Theorie und ihre Tests. Es wird suggeriert, dass die Theorie zu umfassend und komplex ist, um durch ökonometrische Methoden abgedeckt werden zu können. Daher sollte jede ordnungsgemäße Untersuchung auch eine Auseinandersetzung mit vielschichtigen institutionellen Aspekten beinhalten.
Keywords: 330; Wachstumstheorie; Kollektives Handeln